Pengembangan Buku Pop-up Interaktif untuk Meningkatkan Hasil Belajar Kognitif Siswa SD pada Materi Habitat Hewan - Firdausy Zahra Tri Aigistinanda (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research was motivated by the limited availability of engaging educational technology to support elementary science education. The study aimed to develop an interactive pop-up book on animal habitat material for third-grade elementary school students and to evaluate its validity, practicality, and effectiveness. Using a Research and Development (R&D) approach, the development process strictly followed the five phases of the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The field implementation and testing were conducted with third-grade students at SDN 05 Wringinputih. Data were gathered through expert validation sheets, teacher and student questionnaires, and pre-test and post-test instruments. The results from material experts demonstrated a validity score of 93.75% (highly valid), and media experts rated it at 94.2% (highly valid). Practicality evaluations yielded scores of 88.9% from teachers and 86.7% from students, placing the media in the highly practical category. Furthermore, the product's effectiveness was proven by a significant improvement in students' cognitive learning outcomes across levels C1 to C4, with the most notable increase occurring at the analysis level (C4) by 6%. In conclusion, the developed interactive pop-up book is highly valid, practical, and effective, making it a feasible and valuable learning medium to enhance cognitive performance in elementary science education.
FINALISASI oleh Arif 2026 Juni 24
Keywords: ADDIE Model; Animal Habitat; Cognitive Learning Outcomes; Interactive Pop-up Book.